Investigation and assessment of joint mortar mixing ratios used in masonry structures - Yetkin, Musa; Alyamaç, Kürşat Esat; Calayır, Yusuf (My University, 2019)
Masonry structures are brittle structures due to the materials that make up it. This causes the masonry structures to collapse suddenly when exposed to earthquake etc. forces. When the damages seen in masonry structures are examined, it will be seen that the damages mostly originate from masonry unit, joint mortar unit and carrier system. In order to minimize these damages, the properties of the units used to form the masonry structure should be well known. In this study, joint mortar unit used to connect the masonry units to each other and to ensure the interlocking of the system was examined. The factors affecting the joint mortar unit are; joint thickness, mortar material properties, mortar mixing ratios and workmanship. Mortar mixing ratios of these factors were investigated in detail. Cement: lime: sand: water ratios frequently used in experimental studies were determined. Findings obtained as a result of the researches were evaluated.
Bildiri - Yayımlanmış
Keywords: Mortar mixing ratios; Joint mortar; Masonry structures